The Quest For A Cure: A Case Study in the Use of Health Care Alternatives - Kennedy, Dorothy (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1984)
This paper examines the use of health care alternatives by a culturally-conservative Canadian Indian man who suffers from statis ulcers, a disorder he has attributed to both natural and unnatural origins. A case study is presented that utilizes a conceptual framework from medical anthropology. This case study illustrates the cultural and social determinants of health seeking; the perceived etiology, degree of impairment, and the efficacy of the treatment and its cultural relevance are all found to be significant factors in the selection of therapeutic resources. Ritualized performances of Native shamans are found to be an integral part of the healing process.